KEWIRAUSAHAAN, KINERJA KEUANGAN, DAN KELANGGENGAN BISNIS - Fandy Tjiptono (Jurnal Manajemen Indonesia, 2015)
Predicting business longevity using financial performance is one of the interesting topics in accounting and financial management studies. Incorrect prediction of a distressed firm may cause losses to investors, management, creditors and bankers, and inaccurate prediction of a non-distressed company may result in the loss of opportunities. This paper aims to review previous studies using financial performance as the predictor of business longevity in a number of countries. The sources of data include published articles in top international journals. The results indicate that the most dominant approach was bankruptcy prediction models using single and multiple financial ratios. The current paper also identified three main problems in using financial performance as the predictor of business longevity: inconsistent definitions of 'business failure', inconsistent predictive power of financial ratios, and an emphasis on financial symptoms rather than on the more fundamental causes of failure. Managerial implications and research agenda were formulated at the end of this paper